STRATEGI MENINGKATKAN KEPUASAN PELANGGAN DI RITEL MODERN: TINJAUAN DARI ASPEK KUALITAS LAYANAN, PROMOSI, DAN HARGA - Putri Rusdiana Sari; Nurhapsari, Risma; Sholihah, Erlinda; Rahmania, Aftuqa Sholikatur; Kurniawati, Nidya Oktavia; Aninditiyah, Galuh (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study unit is configured to execute an analysis of the influence of service quality, promotion, and price parameters in correlation with the customer satisfaction variable within the modern retail system, with the test object focused on Indomaret, Demak City. The data acquisition and processing procedures are implemented through a quantitative survey mechanism involving 100 respondent entities, utilizing a multiple linear regression algorithm as an analytical instrument to map the relationship between independent variables (service quality, promotion, price) and the dependent variable (customer satisfaction). The calculation results indicate that the service quality, promotion, and price components collectively generate a significant impact on the customer satisfaction variable.